Enterprise Architecture for Enhancing Self-Service Offerings in Digital Channels Within the Telecommunication Industry - Muhamad Rendi Novrian; Erick Dazki (P3M Politeknik Negeri Bengkalis, 2025)
This research aims to analyse the influence of Enterprise Architecture (EA) on Digital Self-care Services (DSS) at PT Wahana Sukses Makmur. The background of this research is based on the company's need to improve the efficiency of digital services through better system integration. However, there are still gaps in the optimal implementation of EA to effectively support DSS. Therefore, this study examines the extent to which EA contributes to improving the quality of the company's digital services. This research uses a quantitative method with a simple linear regression approach. The population in this study were customers of PT Wahana Sukses Makmur, with a sample size of 100 respondents selected through appropriate sampling techniques. Data was collected through a questionnaire that measured customer perceptions of EA implementation and DSS quality. The results showed that EA has a significant influence on DSS, with an F test value of 104.070 and a significance level of 0.000 (p < 0.05). In addition, the t-test results show a regression coefficient of 0.875, which indicates that each one-unit increase in EA implementation will increase the quality of DSS by 0.875 units. Theoretically, this study confirms the important role of EA in supporting DSS development through improved system integration and optimisation of digital processes. The practical implications of this research suggest PT Wahana Sukses Makmur adopt a more structured enterprise architecture to improve operational efficiency, accelerate digital services, and create a more responsive and user-friendly customer experience.